TINJAUAN TERHADAP KONSEP PENDIDIKAN - Syarif, H. Abdullah (STAI Hubbulwathan Duri, 2016)
According to Muhammad Iqbal (educational philosopher from Pakistan), human education has to show the character of the human themselves. Education has to appear the awareness of human about their main character. The characters are sensitivity and strength. The sensitivity means each child has to know the truth of her/his inborn. The strength means each child has the attitude that braced him/herself to hold and interpret the truth in their heart.